Erosive lichen planus: an unmet disease burden - Macken, John H.; Senusi, Amal; O’Toole, Edel A.; Caley, Matthew; Rognoni, Emanuel; Fortune, Farida (Frontiers in Medicine, 2024)
Objectives: To explore the demographic and clinical profile of erosive lichen planus (ELP) across multiple ethnicities within a single cohort, deepening our understanding of disease severity, progression and outcomes. Methods: A longitudinal retrospective cohort study of ELP patients in the ethnically diverse population of East London was carried out, profiling ELP (n=57) against the milder reticular lichen planus (RLP) (n=35).Results: A higher prevalence of ELP was observed in white populations compared to other ethnicities. Affected females were no more likely than males to develop ELP. There was an increased time to diagnosis for ELP patients (median ELP: 452 days, RLP:312 days), spending longer in primary care before onward referral, in particular when referred by their general medical practitioner (GP) (median dentist 313 days, GP: 606 days). Depression was more likely to occur alongside ELP. Being an ex-smoker is a risk factor for ELP while being a current smoker is associated with RLP. A higher proportion of patients with ELP were missing teeth and had periodontal disease. Multisite involvement was more common in ELP, (ELP: 68% RLP: 11.43%). 55% of ELP cases developed scarring and were less likely to respond to first line medications, requiring systemic immunosuppression. The duration of follow up was increased in the ELP who were reviewed for almost twice as long as RLP patients (ELP 71 months RLP 35 months) Conclusions: ELP takes longer to diagnose, requires prolonged tertiary care and is more resistant to treatment, when compared across multiple ethnicities. These patients have increased medical and oral health needs and are at greater risk of scarring than the reticular form. A greater education amongst primary carers on its presentation, as well as a greater understanding of the cellular and molecular mechanisms driving ELP are required to improve diagnostics and identify novel therapeutic approaches.